Global research trends and prospects on immune-related therapy in ischemic stroke: a bibliometric analysis - Wang, Qi; Yuan, Lei; Wang, Fei; Sun, Fei (Frontiers in Cellular Neuroscience, 2024)
Background Following ischemic stroke, non-neuronal cells within the nervous system play a crucial role in maintaining neurovascular unit functions, regulating metabolic and inflammatory processes of the nervous system. Investigating the functions and regulation of these cells, particularly immune cells, deepens our understanding of the complex mechanisms of neuroinflammation and immune modulation after ischemic stroke and provides new perspectives and methods for immune-related therapy. Methods The annual distribution, journals, authors, countries, institutions, and keywords of articles published between 2015 and 2024 were visualized and analyzed using CiteSpace and other bibliometric tools. Results A total of 1,089 relevant articles or reviews were included, demonstrating an overall upward trend; The terms “cerebral ischemia,” “immune response,” “brain ischemia,” “cerebral inflammation,” “neurovascular unit,” and “immune infiltration,” etc. are hot keywords in this field. Conclusion In recent years, research on immune-related therapy for ischemic stroke has focused on mechanisms of occurrence, protection and repair of the blood-brain barrier (BBB) by non-neuronal cells, and regulation of immunosuppression and inflammation. Among these, reducing BBB disruption to minimize secondary brain damage has become a hotspot. At the same time, the complex roles of immune responses have attracted attention, particularly the balance between regulatory T cells and Th17 cells in regulating neuroinflammation and promoting neurological function recovery, which is crucial to reduce secondary neuronal damage and improve prognosis, potentially establishing a pivotal frontier in this domain of investigation.